Management of Gridhrasi (Sciatica) using Panchkarma Therapies – A Case Study - Poriya, Kanji K; Kumar, Vipin (International Research Journal of Ayurveda & Yoga, 2024)
Low back pain is the most common complaint encountered by general practitioners. Chronic low back pain (CLBP) prevalence increases linearly from the third decade of life on, until the 60 years of age, being more prevalent in women. Sciatica is the most common debilitating condition causes CLBP. Radiating leg pain and related disabilities are the observed in sciatica. Nearly 40% of people experience sciatic pain at some point in their life. The diagnosis of sciatica and its management varies considerably within and between countries. Conventional Medicine and surgery are widely used in the management of sciatica. There is a radical rise in the use of Complementary and Alternative Medicine (CAM) in patients with sciatica. Sciatica resembles the disease Gridhrasi which is mentioned in Ayurvedic classical text book which included under Vataja Nanatmaja Vikara. In Gridhrasi, pain starts from Kati-Prushta (pelvic and lumbosacral region) radiating toward Jangha Pada (thigh and legs) with impairment of lifting leg (stiffness). Ghridhrasi can be treated remarkably with procedures of panchakarma and internal medicine. Here in this case study, a 55-year-old male patient was suffering from low back pain radiating toward posterior part of the left leg due to disk desiccation with diffuse disc bulge is seen in MRI at L3-L4 and L4-L5 level and also seen a ligamentum flavum hypertrophy and posterocentral extrusion is seen at L5-S1 level, indenting the anterior thecal sac and mild compression on bilateral exiting nerve roots. He was treated with one course of Kala Basti followed by Bala Taila Aanuvasana Basti and Erandmuladi Kwath Niruha Basti along with Patra Pinda Swedana and Prushtha Basti with Dashmoola Taila and internal medicine. The patient showed improvement remarkably and could do all routine work properly.